Time to recurrence is a significant predictor of cancer-specific survival after recurrence in patients with recurrent renal cell carcinoma: results from a comprehensive multi-centre database (CORONA/SATURN-Project) - Brookman‐May, Sabine D.; May, Matthias; Shariat, Shahrokh F.; Novara, Giacomo; Zigeuner, Richard; Cindolo, Luca; Cobelli, Ottavio De; Nunzio, Cosimo De; Pahernik, Sascha; Wirth, Manfred; Longo, Nicola; Simonato, Alchiede; et al. (BJU international, 2013)
Objectives To assess the prognostic impact of time to recurrence (TTR) on cancer-specific survival (CSS) after recurrence in patients with renal cell carcinoma (RCC) undergoing radical nephrectomy or nephron-sparing surgery. To analyse differences in clinical and histopathological criteria between patients with early and late recurrence. Patients and Methods Of 13 107 patients with RCC from an international multicentre database, 1712 patients developed recurrence in the follow-up (FU), at a median (interquartile range) of 50.1 (25-106) months. In all, 1402 patients had recurrence at ≤5 years (Group A) and 310 patients beyond this time (Group B). Differences in clinical and histopathological variables between patients with early and late recurrence were analysed. The influence of TTR and further variables on CSS after recurrence was assessed by Cox regression analysis. Results Male gender, advanced age, tumour diameter and stage, Fuhrman grade 3-4, lymphovascular invasion (LVI), and pN + stage were significantly more frequent in patients with early recurrence, who had a significantly reduced 3-year CSS of 30% compared with patients in Group B (41%; P = 0.001). Age, gender, tumour histology, pT stage, and continuous TTR (hazard ratio 0.99, P = 0.006; monthly interval) independently predicted CSS. By inclusion of dichotomised TTR in the multivariable model, a significant influence of this variable on CSS was present until 48 months after surgery, but not beyond this time. Conclusions Advanced age, male gender, larger tumour diameters, LVI, Fuhrman grade 3-4, pN + stage, and advanced tumour stages are associated with early recurrence. Up to 4 years from surgery, a shorter TTR independently predicts a reduced CSS after recurrence.